PERKEMBANGAN PENDIDIKAN ISLAM - Ahmad Kholil (Turatsuna : Jurnal Keislaman dan Pendidikan, 2019)
Since 2000 until now, in Kambingan village, Tumpang District, Malang Regency, there have been two RA level formal education, two basic level formal education, two non-formal education at the ula and wustho level, and two Majlis Taklim Riyadlul Jannah and Jakfar Mania. The success of Kambingan village, Tumpang District, Malang Regency in developing Islamic education is for the role of the religious community the majority of the nahdliyyin group. With a high spirit of togetherness, the development of Islamic education in the village of Kambingan, Tumpang District, Malang Regency significantly created. Keywords: Development of Islamic Education  Sejak tahun 2000 sampai dengan sekarang, di desa Kambingan Kecamatan Tumpang Kabupaten Malang sudah terdapat dua pendidikan formal tingkat RA, dua pendidikan formal tingkat dasar, dua pendidikan non formal tingkat ula dan wustho, dan dua Majlis Taklim Riyadlul Jannah dan jakfar mania. Keberhasilan desa Kambingan Kecamatan Tumpang Kabupaten Malang dalam mengembagkan pendidikan Islam adalah atas peran serta masyarakat yang religi mayoritas golongan nahdliyyin. Dengan semangat kebersamaannya yang cukup tinggi, maka terciptalah perkembangan pendidikan Islam di desa Kambingan Kecamatan Tumpang Kabupaten Malang secara signifikan. Kata Kunci : Perkembangan Pendidikan Islam